Memaksimalkan Perkembangan Kognitif Anak Sekolah Dasar Melalui Pembelajaran Literasi - Titik Suciati (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2017)
Being able to explore the world around through the five senses is one of the stages of cognitive development that passes through each individual. Then, just how to maximize each stage to get the perfect cognitive ability. Especially in elementary school-aged children, they know more about many things than before, and need good guidance on how to learn from the surrounding environment as a preparation for the next stage of cognitive development. Cognitive or intellectual potential is imposed on the activities of thinking that actually need an intensive effort to maximize it. One that can be done is through literacy learning. Literacy learning at elementary school level is hoped as the process of understanding, the process of reading, the process of writing, and the concept of written analysis that can help to improve their cognitive development. While in the context of education, there are four forms of learning that can be applied, they are learning of literacy reading, literacy learning writing, science literacy learning, learning mathematical literacy.